Primary ileal villous atrophy is often associated with microscopic colitis. Issue 4 (1st October 1997) - Marteau, P; Lavergne-Slove, A; Lemann, M; Bouhnik, Y; Bertheau, P; Becheur, H; Galian, A; Rambaud, J C
Abstract : Three cases of apparent primary villous atrophy of the terminal ileum in women with chronic diarrhoea are reported. Eight cases have previously been reported in the literature. Clinical characteristics are the presence of severe chronic secretory diarrhoea with episodes of hypokalaemia combined with signs of ileal malabsorption and/or efficacy of cholestyramine. Diagnosis is based on ileoscopy and histology. An association with microscopic colitis was present in the three patients and in four cases in the literature. The pathogenesis of primary ileal villous atrophy remains unknown and may involve dysimmunity. Its association with microscopic colitis may indicate a common pathogenesis or support the hypothesis that the faecal stream or bile salts play a role in the pathogenesis of microscopic colitis.